Time-Frequency Characteristics of Ground Motion and Seismic Response Analysis of Typical Structures in the Yangbi Earthquake in Yunnan Province - Qin Xu; Shaofeng Chai; Shihu Zhou; Liqun Bao; Quan Li (Advances in Civil Engineering)
The ground motion records obtained by the CDSMON during the Ms6.4 earthquake in Yangbi, Yunnan Province, on May 21, 2021, were subjected to routine processing such as baseline correction and filtering. The nonstationary time-frequency characteristics of ground motion signals were analysed by the wavelet transform, and the acceleration response spectrum characteristics of typical stations under different epicentral distances, magnitudes, and site conditions were analysed. Finite element software was used to establish a model to analyse the seismic response of a typical three-span continuous beam bridge. The maximum peak ground acceleration (PGA) of this earthquake (720.29 gal) was obtained from 53YBX in the NS direction at the epicentral distance of 8.6 km. The energy at station 53YBX was mainly concentrated in 0–15 Hz range, and the low-frequency component energy caused great damage to buildings with natural frequencies in this frequency band. The Sa value near the origin of the earthquake is relatively large, as the distance from the epicentre increases, the predominant period of Sa also gradually increases, and the high-frequency component diminishes. With the increase in earthquake magnitude, the Sa peak increased, and the long-period component became more obvious. The soil station had more obvious long-period components than the bedrock station, which is consistent with the amplification result of the response spectrum of overburden thickness to surface acceleration. The earthquake had little influence on the pier displacement of the three-span continuous beam bridge with a fundamental period of 0.77 s but had a great influence on the bending moment at the bottom of the piers.